PERLINDUNGAN HUKUM TERHADAP PELAPOR DALAM TINDAK PIDANA NARKOTIKA DI KEPOLISIAN RESOR KAMPAR - Ahmad Novrian Arsyad; Evi Deliana; Elmayanti Elmayanti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
To effort and eliminate drugs crime in Kampar need some action of the people to report that crime to the Police Department and became a witness. To convincing people to make sure them reported the drugs crime need some real action from the Police side who duty on it to protected them, wich is the protction is really importent because the protection is the only way to convince people society to report. And the witness it self are important component and is a key to reveal every single case of drugs crimes. To push the limit of drugs crime in Kampar as we known is higher level every year need someone to reporting it and to prevent it and ofcially to counter it while the crime is happened. On this thesis the problem appointed is how the police department protecting an informan in Kampar Police Department territory? And what the obstruct factor to protected the informan? The purpose of this research is to know how Kampars Police Deparment protecting the informan oncrimanl dugs caseand to knowing what the obstruct of Kampar Police Departmentin case proecting theinforman on crimanaldrugs case in Kampar. The method of this research is Sociological Law Method. The data that the writer has is the premier and seconds datawich is processed bya kualitatif way. Depend on the research we do on a discuss chapter and the we finally got one conclusion the effort of protecting an informan in Kampar territory Kampar Police Department do two protecion type wich is preventif protection and represif protection. The preventif proection is the protection wich is do by prevent something that can threatening and endanger public order and peace. And then represif protection is wich is failed to do a preventif protection by seeking a prepetator. During a do protecting to an informan founded a obstruct to tha protection wich is : 1. The fasilities to do a protection to an infoman itself. 2. The people. 3. The law enforcer.Keyword: Informan – Criminal – Drugs – Law Protection